Cerium-manganese solid solution material taking manganese dioxide as main body as well as preparation method and application of cerium-manganese solid solution material

By adding cerium ions into the manganese dioxide lattice to form a cerium manganese solid solution material, the problem of traditional manganese dioxide is solved, and the charge transfer efficiency and electrochemical performance are significantly improved. It is suitable for supercapacitors.

CN119822410APending Publication Date: 2025-04-15SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510024398.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional pure phase manganese dioxide has low conductivity, resulting in high charge transfer resistance, limiting its application range in supercapacitors.

Method used

By incorporating tetravalent and trivalent cerium ions into the manganese dioxide lattice, a cerium-manganese solid solution material is formed, which improves charge transfer efficiency and electrochemical performance.

Benefits of technology

The specific capacitance value of cerium manganese solid solution materials has increased by more than 35%, significantly improving the electrochemical properties of traditional manganese dioxide and is suitable for the preparation of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822410A_ABST
    Figure CN119822410A_ABST
Patent Text Reader

Abstract

The invention discloses a cerium-manganese solid solution material taking manganese dioxide as a main body and a preparation method of the cerium-manganese solid solution material, and belongs to the technical field of inorganic non-metallic material preparation and supercapacitors. The cerium-manganese solid solution material is specifically synthesized by adopting a homogeneous precipitation method and ventilating sintering at room temperature and is a single-phase composite material different from a manganese dioxide composite material, tetravalent and trivalent cerium ions are doped into manganese dioxide crystal lattices to form a cerium-manganese solid solution, and the charge transfer efficiency of traditional pure-phase manganese dioxide is further improved; the electrochemical performance of the traditional pure-phase manganese dioxide is further improved, and the method can be applied to the field of supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a cerium-manganese solid solution material with manganese dioxide as a main component, and a preparation method and application thereof. Background Art

[0002] Research status of MnO2 in supercapacitor materials: The skeleton of MnO2 itself is formed by the close-packed cubic octahedron formed by [MnO6] and oxygen atoms in the form of coordination bonds. The oxygen atoms are located at the vertices of the octahedron, while the manganese atoms are located at the body center of the entire octahedron. In the [MnO6] octahedron, the common edges are connected to form single-chain, double-chain and multi-chain structures. Different chains then form tunnel structures with gaps through the common vertices. Since the [MnO6] octahedron has a variety of different stacking formation methods and the valence states of manganese are more, the crystal structure of manganese dioxide is very complex and there are many types of crystal forms. MnO2 has received widespread attention in the field of energy storage due to its high theoretical specific capacity, low energy density, low price and environmental protection. Due to its low cost, good thermal, chemical and environmental stability, nanostructured MnO2 electrode materials are often used in the field of electrochemistry. They have good electronic properties, easy proton and electron transfer pathways, and good reversible redox reactions. Among different metal oxides, MnO2 is considered to be one of the promising inorganic materials due to its simple synthesis process, low cost and excellent electrochemical performance. However, MnO2 electrode materials are only micrometers thick. Due to their low conductivity and high charge transfer resistance, their specific capacitance is generally small, which greatly limits their application range. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a cerium-manganese solid solution material with manganese dioxide as the main body, and a preparation method and application thereof. Specifically, by adding tetravalent and trivalent cerium ions into the manganese dioxide lattice to form a cerium-manganese solid solution, the charge transfer efficiency of the traditional pure phase manganese dioxide is further improved, and the electrochemical performance of the traditional pure phase manganese dioxide is improved, and it can be applied to the field of supercapacitors.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0005] A cerium-manganese solid solution material with manganese dioxide as the main component is formed by doping tetravalent and trivalent cerium ions into the manganese dioxide lattice. Its chemical composition expression in terms of atomic ratio is Mn X Ce Y O2, where: X = 1, Y = 0.01-0.1.

[0006] The cerium-manganese solid solution material is composed of cerium dioxide and manganese dioxide, and is in the form of a single manganese dioxide phase.

[0007] The particle size of the cerium manganese solid solution material is 5-10nm, and the purity is more than 90%; the capacitance value of the cerium manganese solid solution is increased by more than 35% compared with commercial manganese dioxide.

[0008] The method for preparing the cerium-manganese solid solution material with manganese dioxide as the main body is to prepare it by adopting a uniform precipitation method combined with ventilation sintering, and the method specifically comprises the following steps:

[0009] (1) weighing a certain proportion of cerium acetate and manganese acetate powder and dissolving them in deionized water at room temperature, stirring until a clear and transparent mixed solution is obtained; and preparing a certain amount of ammonium carbonate solution;

[0010] (2) using a rubber-tipped dropper, slowly add the mixed solution obtained in step (1) to the ammonium carbonate solution. After all the additions are completed, continue stirring the reaction for 2-3 hours and let it stand for 0.5-1 hour;

[0011] (3) filtering the product obtained after the reaction in step (2), taking the precipitate, washing it with deionized water and anhydrous ethanol for 5 to 6 times, and then drying it in an oven;

[0012] (4) placing the product obtained after drying in step (3) in a tube furnace for ventilation calcination;

[0013] (5) preparing a nitric acid solution of a certain concentration; pouring the product obtained after calcination in step (4) into the nitric acid solution, and then placing it in a water bath pot for heating and stirring, the water bath temperature is 70° C. to 90° C., the stirring speed is 250 r / min to 350 r / min, and the stirring time is 1.5 h to 2.5 h;

[0014] (6) Filter the product obtained in step (5), take the precipitate, wash it with deionized water and anhydrous ethanol for 5 to 6 times, put it into an oven for drying, and the black solid obtained after drying is the cerium-manganese solid solution material.

[0015] Furthermore, in step (1), the molar ratio of cerium acetate to manganese acetate is (0-1):10, the total concentration of metal ions in the mixed solution is 0.2 mol / L-0.7 mol / L, and the concentration of ammonium carbonate solution is 1 mol / L-3 mol / L.

[0016] Furthermore, in step (2), the volume ratio of the mixed solution to the ammonium carbonate solution is 1:(0.5-5); when the mixed solution is slowly added dropwise using a rubber-tipped dropper, the addition method is a small amount and multiple times, and the amount added each time is 1mL to 2mL. The slow addition is to allow the cerium acetate and manganese acetate in the mixed solution to react completely with the ammonium carbonate, and to allow the cerium ions and manganese ions to be evenly mixed in the process of generating a precipitate.

[0017] Furthermore, in step (4), the calcination temperature is 400° C. to 600° C., and the holding time is 9 to 11 hours; the ventilation calcination enables the monovalent manganese ions to fully contact with the oxygen ions in the air, thereby obtaining more tetravalent manganese ions to produce manganese dioxide.

[0018] Furthermore, in step (5), the ratio of the product obtained after calcination in step (4) to the nitric acid solution is 100g:(100-500)mL; the concentration of the nitric acid solution is 0.1mol / L-0.2mol / L, and the nitric acid solution can dissolve most of the trivalent manganese ions after heating and stirring in a water bath, thereby obtaining a purer cerium-manganese solid solution with manganese dioxide as the main component.

[0019] Furthermore, in step (3) and step (6), the drying temperature is 100° C. to 130° C., and the insulation time is 23 to 25 hours.

[0020] The cerium-manganese solid solution material with manganese dioxide as the main component can improve the charge transfer efficiency of traditional pure-phase manganese dioxide, thereby improving the electrochemical performance of traditional pure-phase manganese dioxide, and can be applied to the preparation of supercapacitors.

[0021] The design mechanism and beneficial effects of the present invention are as follows:

[0022] 1, traditional manganese dioxide material is lower because of its electrical conductivity, and charge transfer resistance is higher, so cause specific capacitance value less, and cerium oxide material has more oxygen vacancies, can improve the conductivity and electrochemical characteristics of material by electron delocalization around oxygen, manganese dioxide and cerium oxide material belong to tetragonal phase structure again, and the two lattice constants are almost the same, so the two have the possibility of becoming solid solution.Ammonium carbonate is utilized to provide abundant alkaline environment in the present invention, and uniform precipitation method is utilized again, manganese ion and cerium ion are mixed in the process of forming precipitation, form the intermediate product (manganese carbonate) of single phase, and subsequently by ventilation sintering, provide oxygen-rich sintering environment for intermediate product, make monovalent manganese ion and cerium ion become trivalent and tetravalent cerium manganese ion, finally by tetravalent manganese ion and trivalent manganese ion solubility in nitric acid of certain concentration is different, utilize nitric acid solution water bath stirring to dissolve most trivalent manganese ion, thereby obtain purer cerium manganese solid solution material with manganese dioxide as main body.

[0023] 2. The raw materials used in the present invention are simple and safe, which avoids the situation where other transition metal oxides are used to modify the MnO2 electrode material, but the cost is greatly increased accordingly.

[0024] 3. The cerium-manganese solid solution synthesized in the present invention has finer particles and higher purity, which is beneficial to the electrochemical properties of manganese dioxide.

[0025] 4. The present invention forms a cerium-manganese solid solution by doping tetravalent and trivalent cerium ions into the manganese dioxide lattice, so that the trivalent and tetravalent manganese ions and the tetravalent and trivalent cerium ions may undergo redox reactions with each other, thereby generating more holes and charge carriers, further improving the charge transfer efficiency of traditional pure phase manganese dioxide, and at the same time improving the electrochemical properties of traditional pure phase manganese dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 MnCe 0.1 X-ray diffraction patterns of cerium-manganese solid solution before and after cleaning and before sintering.

[0027] Figure 2 MnCe 0.1 Physical picture of cerium-manganese solid solution.

[0028] Figure 3 MnCe 0.1 Cyclic CV curves at scan rates of 1mV / s, 5mV / s, 10mV / s, 20mV / s, 50mV / s, 100mV / s, and 200mV / s.

[0029] Figure 4 The cyclic CV curves of commercial manganese dioxide at scanning speeds of 1mV / s, 5mV / s, 10mV / s, 20mV / s, 50mV / s, 100mV / s, and 200mV / s. DETAILED DESCRIPTION

[0030] The present invention is described in detail below in conjunction with the accompanying drawings and examples, but is not intended to limit the present invention. The preparation method of the cerium-manganese solid solution material with manganese dioxide as the main component in the present invention comprises the following steps:

[0031] 1. At room temperature, weigh cerium acetate and manganese acetate powders in corresponding proportions according to the molar ratio of cerium and manganese in the cerium-manganese solid solution material to be prepared, and dissolve them in 100 mL of deionized water, keeping the total concentration of metal ions in the obtained mixed solution at 0.2 mol / L to 0.7 mol / L, stir evenly until the mixed solution is clear and transparent, and then prepare 200 ml of ammonium carbonate solution with a solution concentration of 1 mol / L to 3 mol / L;

[0032] 2. Use a rubber-tipped dropper to slowly drop the mixed solution of cerium acetate and manganese acetate into the ammonium carbonate solution in small amounts and multiple times. The amount of each drop is 1mL~2mL. The slow drop is to allow cerium acetate and manganese acetate to react completely with ammonium carbonate, and to mix cerium ions and manganese ions evenly in the process of forming a precipitate. After all the drops are added, continue stirring for 2-3 hours and let stand for 0.5-1 hour.

[0033] 3. Filter the product obtained in step 2, take the precipitate, wash it with deionized water and anhydrous ethanol for 5 to 6 times, put it into an oven for drying at a temperature of 100°C to 130°C, and keep it warm for 23 to 25 hours.

[0034] 4. The product obtained in step 3 is placed in a tubular furnace for ventilation calcination at a temperature of 400° C. to 600° C. for a holding time of 9 to 11 hours. Ventilation sintering can allow the monovalent manganese ions to fully contact with the oxygen ions in the air, thereby obtaining more tetravalent manganese ions to produce manganese dioxide.

[0035] 5. Prepare a nitric acid solution with a concentration of 0.1 mol / L to 0.2 mol / L, pour all the product obtained after calcination in step 4 into the nitric acid solution (the ratio of the product obtained after calcination to the nitric acid solution is 100 g: (100-500) mL), then place it in a water bath for heating and stirring, the water bath temperature is 70° C. to 90° C., the speed is 250 r / min to 350 r / min, and the stirring time is 1.5 h to 2.5 h. Most of the trivalent manganese ions are dissolved by the different solubilities of trivalent manganese ions and tetravalent manganese ions in a nitric acid solution of a certain concentration, thereby obtaining a purer cerium-manganese solid solution with manganese dioxide as the main body.

[0036] 6. Filter the product obtained in step 5, take the precipitate, wash it with deionized water and anhydrous ethanol for 5 to 6 times, put it into an oven for drying at a temperature of 100° C. to 130° C. for 23 to 25 hours, and finally obtain a black solid, which is the cerium-manganese solid solution material.

[0037] Example 1

[0038] The cerium-manganese solid solution prepared in this embodiment is MnCe 0.1 , the specific process is as follows:

[0039] (1) At room temperature, 0.157 g of cerium acetate and 12.132 g of manganese acetate powder were weighed and dissolved in 100 mL of deionized water, and the mixture was stirred evenly until the mixed solution was clear and transparent. 38.436 g of ammonium carbonate powder was weighed and dissolved in 200 mL of deionized water, and the mixture was stirred evenly until the solution was clear and transparent.

[0040] (2) The ammonium carbonate solution was continuously stirred, and the mixed solution of cerium acetate and manganese acetate was added to the ammonium carbonate solution in small amounts and multiple times using a rubber-tipped dropper. The amount added each time was 1 mL to 2 mL. The mixture was continuously stirred for 2 h and allowed to stand for 0.5 h.

[0041] (3) The obtained product was filtered, and the precipitate was washed with deionized water and anhydrous ethanol for 6 times, and then placed in an oven for drying at 120°C for 24 hours. The obtained product (MnCe 0.1 Ammonium carbonate precipitation) XRD spectrum Figure 1 .

[0042] (4) The obtained product was placed in a tube furnace for ventilation calcination at a temperature of 500°C for 10 h. The calcined product (500°C, 10 h MnCe 0.1 )XRD spectrum Figure 1 .

[0043] (5) 128 mL of deionized water and 1 mL of concentrated nitric acid were used to prepare a 0.14 mol / L nitric acid solution, and all the powder sintered in step (4) was poured into the solution. The solution was then placed in a water bath and heated with stirring. The water bath temperature was 80° C., the rotation speed was 300 r / min, and the stirring time was 2 h.

[0044] (6) The obtained product was filtered, and the precipitate was taken out and washed with deionized water and anhydrous ethanol for 6 times, and then placed in an oven for drying at a temperature of 120° C. for 24 hours. The black solid obtained was the cerium-manganese solid solution material after washing. 0.1 ), chemical formula is MnCe 0.1 The X-ray diffraction pattern of the final solid solution material is as follows: Figure 1 As shown, the actual Figure 2 As shown, the grain size of the cerium-manganese solid solution sample is calculated to be 6.3 nm by the diffraction peak width in the XRD spectrum; the purity of the obtained cerium-manganese solid solution material is greater than or equal to 91%.

[0045] Example 2

[0046] The MnCe prepared in Example 1 0.1 The CV curve test of cerium manganese solid solution and commercial manganese dioxide in electrochemical testing is as follows:

[0047] (1) MnCe 0.1 Cerium manganese solid solution powder, carbon black and PVDF were mixed uniformly in a weight ratio of 8:1:1 to obtain a mixed powder. 5 mg of the mixed powder was added with 100 ul of NMP solution and 5 ul of Nafion perfluorinated resin solution. The mixture was ultrasonicated in an ultrasonic machine for 30 min, and then uniformly coated on the 1×1 mm below the conductive glass. The mixture was placed in an electric hot air drying oven, first dried at 40°C for 24 h, and then dried at 100°C for 2 h to obtain a working electrode. The working electrode was tested using an electrochemical workstation model CHI760E. The scanning speeds of the test were 1 mV / s, 5 mV / s, 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s, and 200 mV / s. The results were as follows: Figure 3 The cyclic CV curve diagram shown.

[0048] (2) Commercial manganese dioxide powder, carbon black and PVDF were mixed in a weight ratio of 8:1:1 to obtain a mixed powder. 5 mg of the mixed powder was added with 100 ul of N-methylpyrrolidone solution (NMP) and 5 ul of Nafion perfluorinated resin solution. The mixture was ultrasonicated in an ultrasonic machine for 30 min. The mixture was evenly coated on the 1×1 mm area below the conductive glass. The mixture was placed in an electric hot air drying oven and dried at 40°C for 24 h and then at 100°C for 2 h to obtain a working electrode. The working electrode was tested using a CHI760E electrochemical workstation at scanning speeds of 1 mV / s, 5 mV / s, 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s and 200 mV / s. The results were: Figure 4 The cyclic CV curve diagram shown.

[0049] from Figure 3 and Figure 4 It can be seen that under the same test conditions, after the trivalent and tetravalent cerium ions are integrated into the manganese dioxide lattice to form a cerium-manganese solid solution, its CV area is significantly larger than the CV area of ​​commercial manganese dioxide, indicating that the trivalent and tetravalent manganese ions, tetravalent and trivalent cerium ions undergo redox reactions with each other, generating more holes and charge carriers, further improving the charge transfer efficiency of traditional pure phase manganese dioxide. By calculation, it can be concluded that the capacitance value of commercial manganese dioxide at a scanning speed of 5mV / s is 112.29F / g, and MnCe 0.1 The capacitance value of cerium manganese solid solution is 154.39F / g at a scanning rate of 5mV / s. 0.1 The specific capacitance of cerium manganese solid solution increased by 137.49% compared with commercial manganese dioxide.

[0050] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.

Claims

1. A cerium-manganese solid solution material with manganese dioxide as the main component, characterized in that: The cerium-manganese solid solution material is formed by doping tetravalent and trivalent cerium ions into the manganese dioxide lattice, and its chemical composition expression in terms of atomic ratio is Mn X Ce Y O2, where: X = 1, Y = 0.01-0.

1.

2. The cerium-manganese solid solution material with manganese dioxide as the main component according to claim 1, characterized in that: The cerium-manganese solid solution material is composed of cerium dioxide and manganese dioxide, and exhibits a single phase of manganese dioxide.

3. The cerium-manganese solid solution material with manganese dioxide as the main component according to claim 1, characterized in that: The particle size of the cerium manganese solid solution material is 5-10nm, and the purity is more than 90%. Compared with commercial manganese dioxide, the capacitance value of the cerium manganese solid solution is increased by more than 35%.

4. The method for preparing the cerium-manganese solid solution material with manganese dioxide as the main component according to claim 1, characterized in that: The method adopts a uniform precipitation method combined with ventilation sintering to prepare the cerium-manganese solid solution material, and the method specifically comprises the following steps: (1) weighing a certain proportion of cerium acetate and manganese acetate powder and dissolving them in deionized water at room temperature, stirring until a clear and transparent mixed solution is obtained; and preparing a certain amount of ammonium carbonate solution; (2) using a rubber-tipped dropper, slowly add the mixed solution obtained in step (1) to the ammonium carbonate solution. After all the additions are completed, continue stirring the reaction for 2-3 hours and let it stand for 0.5-1 hour; (3) filtering the product obtained after the reaction in step (2), taking the precipitate, washing it with deionized water and anhydrous ethanol for 5 to 6 times, and then drying it in an oven; (4) placing the product obtained after drying in step (3) in a tube furnace for ventilation calcination; (5) preparing a nitric acid solution of a certain concentration; pouring the product obtained after calcination in step (4) into the nitric acid solution, and then placing it in a water bath pot for heating and stirring, the water bath temperature is 70° C. to 90° C., the stirring speed is 250 r / min to 350 r / min, and the stirring time is 1.5 h to 2.5 h; (6) Filter the product obtained in step (5), take the precipitate, wash it with deionized water and anhydrous ethanol for 5 to 6 times, put it into an oven for drying, and the black solid obtained after drying is the cerium-manganese solid solution material.

5. The method for preparing a cerium-manganese solid solution mainly composed of manganese dioxide according to claim 4, characterized in that: In step (1), the molar ratio of cerium acetate to manganese acetate is (0-1):10, the total concentration of metal ions in the mixed solution is 0.2 mol / L-0.7 mol / L, and the concentration of the ammonium carbonate solution is 1 mol / L-3 mol / L.

6. The method for preparing a cerium-manganese solid solution mainly composed of manganese dioxide according to claim 5, characterized in that: In step (2), the volume ratio of the mixed solution to the ammonium carbonate solution is 1:(0.5-5); when the mixed solution is slowly added dropwise using a rubber-tipped dropper, the dropping method is a small amount and multiple times, and the amount of each drop is 1mL to 2mL. The slow dropping is to allow the cerium acetate and manganese acetate in the mixed solution to react completely with the ammonium carbonate, and to allow the cerium ions and manganese ions to be evenly mixed in the process of generating a precipitate.

7. The method for preparing a cerium-manganese solid solution mainly composed of manganese dioxide according to claim 4, characterized in that: In step (4), the calcination temperature is 400° C. to 600° C., and the holding time is 9 to 11 hours. Ventilated calcination allows the monovalent manganese ions to fully contact with oxygen ions in the air, thereby obtaining more tetravalent manganese ions to produce manganese dioxide.

8. The method for preparing a cerium-manganese solid solution mainly composed of manganese dioxide according to claim 4, characterized in that: In step (5), the concentration of the nitric acid solution is 0.1 mol / L to 0.2 mol / L, and the ratio of the product obtained after calcination in step (4) to the nitric acid solution is 100 g: (100-500) mL; after heating and stirring in a water bath, the nitric acid solution can dissolve most of the trivalent manganese ions, thereby obtaining a purer cerium-manganese solid solution with manganese dioxide as the main component.

9. The method for preparing a cerium-manganese solid solution mainly composed of manganese dioxide according to claim 4, characterized in that: In step (3) and step (6), the drying temperature is 100° C. to 130° C., and the insulation time is 23 to 25 hours.

10. The use of the cerium-manganese solid solution material with manganese dioxide as the main component according to any one of claims 1 to 3, characterized in that: The cerium-manganese solid solution material with manganese dioxide as the main component can improve the charge transfer efficiency of traditional pure-phase manganese dioxide, thereby improving the electrochemical properties of traditional pure-phase manganese dioxide, and can be applied to the preparation of supercapacitors.